Effect of Hydro-mulch and Geo-jute Application on the Soil Loss during Cultivation of Corn (Zea Mays L.) in Dry Land - Dwi Rustam Kendarto; Raka Putra Pratama; Kharistya Amaru (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
Utilization up-land area for cultivating strategic food crops (paddy, corn and soybean) often neglects the rules of conservation so that it caused surface soil loss by run off. These events can reduce the fertility of agricultural land, so that it results in a decrease in land productivity and finally cause critical lands. Alternative conservation techniques that can be carried out through the application of hydro-mulch and geo-jute combination in order to reduce surface soil loss. The purpose of this study is to examine the use of hydro-mulch and geo-jute in reducing soil loss and observing maize growth as one of the effects of soil loss due to erosion. The treatments given are hydro-mulch, geo-jute and combination of hydro-mulch and geo-jute. The study showed that alternative conservation techniques in the form of hydro-mulch and geo-jute application proved to be able to reduce the amount of soil loss. The combination of hydro-mulch and geo-jute has the ability to reduce the amount of soil loss due to rainfall by 31.51%. Plot with geo-jute treatment can reduce soil loss by 21.86%, and plot with hydro-mulch treatment can reduce soil loss by 11.92%. The hydro-mulch and geo-jute combination can increase the growth of corn. Keywords:  Alternative, Erosion, Geo-jute, Hydro-mulch